Vocal apparitions : the attraction of cinema to opera - Grover-Friedlander, Michal (Princeton studies in opera., 2005)
"Cinema and opera have become intertwined in a variety of powerful and unusual ways. Vocal Apparitions tells the story of this fascinating intersection, interprets how it occurred, and explores what happens when opera is projected onto the medium of film."--Jacket